PENGARUH PENDEKATAN MATEMATIS REALISTIK TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Ilmi Aliyah Firdaus; Irwani Zawawi; Sri Suryanti (IKIP Siliwangi, 2022)
The research was conducted with the aim of knowing mathematic learning with a realistic mathematics approach has an effect on the ability to understand students’ mathematical concepts better. Conducted using a quasi-experimental research type, the learning process applied involves two types of classes, namely the experimental class and the control class. PMR-based learning is used in the experimental class, while the control class is used for conventional learning. Considering that mathematics lessons cannot be separated from students' creative learning abilities, in addition to the posttest only control design in the form of a final test of understanding the concept of research instruments, such as learning creativity questionnaire sheets are also given to students. Using Statistical Product and Service Solutions (SPSS) data analysis techniques with a probability value (significant) of 5%, it shows a positive influence which means that H0 is rejected and H1 is accepted. Based on the descriptive data obtained, it is known that the mean posttest learning outcomes in the experimental class (PMR) are greater than the control class (conventional), which illustrates the application of learning using PMR has a significant influence on the ability to understand mathematical concepts and learning creativity of class VIII SMP Muhammadiyah 1 Babat.